Tetraspanins as Potential Therapeutic Candidates for Targeting Flaviviruses - Ahmed, Waqas; Neelakanta, Girish; Sultana, Hameeda (Frontiers in Immunology, 2021)
Tetraspanin family of proteins participates in numerous fundamental signaling pathways involved in viral transmission, virus-specific immunity, and virus-mediated vesicular trafficking. Studies in the identification of novel therapeutic candidates and strategies to target West Nile virus, dengue and Zika viruses are highly warranted due to the failure in development of vaccines. Recent evidences have shown that the widely distributed tetraspanin proteins may provide a platform for the development of novel therapeutic approaches. In this review, we discuss the diversified and important functions of tetraspanins in exosome/extracellular vesicle biology, virus-host interactions, virus-mediated vesicular trafficking, modulation of immune mechanism(s), and their possible role(s) in host antiviral defense mechanism(s) through interactions with noncoding RNAs. We also highlight the role of tetraspanins in the development of novel therapeutics to target arthropod-borne flaviviral diseases.